CONNECTED DOMINATING SET IN INTERVAL-VALUED FUZZY GRAPHS - AL-Ahmadi, Faisal M.; Shubatah, Mahiuob M. Q. (IJRDO -JOURNAL OF MATHEMATICS, 2022)
The connected domination is one of the important issues in mathematics and other science. In This paper, connected domination in interval-valued fuzzy graphs is defined and studied. Some bounds on connected domination number γc(G) is provided for sev- eral interval-valued fuzzy graphs. Furthermore, the relationship of γc(G) with some other known parameters in interval-valued fuzzy graphs are investigated with some suit- able examples.